From Competence to self-efficacy: measuring student progress in translation company simulations - Konttinen, Kalle (fi=Turun yliopisto|en=University of Turku|, 2022)
This dissertation investigates how the professional abilities of translation students can be monitored in translation company simulation courses. Translation company simulation is a pedagogical approach in which students carry out translation projects in self-organising teams. A broad set of translation production workflow activities is explored from two angles: 1) students’ understanding of the activities and 2) theoretical conceptualisations of the abilities required for performing them. For measuring progress, the construct of self-efficacy is proposed to complement the construct of competence. A translation service provision self-efficacy model is designed as a theoretical framework and operationalised as a survey instrument for monitoring student progress. The dissertation comprises five previously published articles and a thesis summary. The first article presents the simulation course and introduces a multicomponent competence model for identifying students’ abilities. The second article explores translation students’ understanding of workflow from a competence perspective through content analysis of essays. The third article introduces a meta-level model of revision and post-editing competence and defines their place within the simulation and the translator education curriculum. The fourth article shifts the perspective from competence to self-efficacy and constructs a translation service provision model based on a translation service provision standard and a business process model of a translating organisation. Exploratory and confirmatory factor analysis is used to operationalise the model as a survey scale. The fifth article tests the scale using longitudinal multilevel modelling. A theoretical contribution is the translation service provision model that organises various business processes and workflow activities into a coherent whole. A methodological result is the translation service provision self-efficacy scale and the method for analysing self-efficacy through multilevel modelling. The findings support that translation company simulations enhance students’ self-efficacy in translation management and translation-related tasks. The results may have theoretical and practical implications for the pedagogy of translation company simulations.

Tutkin väitöskirjassani, miten kääntämisen opiskelijoiden ammatillisten valmiuksien kehittymistä voidaan seurata käännösyrityssimulaatiokursseilla. Käännösyrityssimulaatio on pedagoginen menetelmä, jossa opiskelijat toteuttavat käännösprojekteja itseorganisoituvissa tiimeissä. Tutkin käännöstuotannon työnkulun toimintoja kahdesta näkökulmasta: 1) opiskelijoiden käsitystä toiminnoista ja 2) valmiuksien käsitteellistämistä. Tutkimukseni päätyy ehdottamaan minäpystyvyyttä täydentäväksi vaihtoehdoksi kompetenssiin perustuville mittauksille. Mittausten teoreettiseksi viitekehykseksi kehitän käännöspalveluiden tuottamisen minäpystyvyysmallin. Operationalisoin mallin kyselyinstrumentiksi ja testaan käännösyrityssimulaatiossa mallin soveltuvuutta opiskelijoiden edistymisen kuvaamiseen. Väitöskirja sisältää viisi aiemmin julkaistua artikkelia sekä yhteenvedon. Ensimmäinen artikkeli esittelee simulaatiokurssin ja luo monikomponenttisen kompetenssimallin opiskelijoiden valmiuksien kuvaamiseen. Toinen artikkeli tutkii sisällönanalyysin avulla kääntämisen opiskelijoiden käsityksiä käännösprojektin työnkulusta. Kolmas artikkeli esittelee metatason mallin käännöksentarkistuksen ja jälkieditoinnin kompetenssien kuvaamiseen ja määrittelee näiden toimintojen aseman simulaatiokurssilla sekä kääntäjänkoulutuksen opetussuunnitelmassa. Neljäs artikkeli rakentaa käännöspalvelujen minäpystyvyysmallin ja operationalisoi sen minäpystyvyyskyselyksi. Viides artikkeli testaa minäpystyvyyskyselyä käännösyrityssimulaatiossa. Väitöskirjan teoreettinen tulos on käännöspalvelujen tarjoamisen malli, joka jäsentää käännösorganisaation erilaiset liiketoimintaprosessit ja työnkulun toiminnot yhtenäiseksi kokonaisuudeksi. Menetelmien osalta keskeinen tulos on käännöspalvelujen tarjoamisen minäpystyvyyskysely sekä menetelmä minäpystyvyyden analysoimiseksi monitasomallinnuksen avulla. Käytännön tulokset viittaavat siihen, että käännösyrityssimulaatiot lisäävät opiskelijoiden alakohtaista minäpystyvyyttä käännösprojektinhallinnassa ja kääntämiseen liittyvissä tehtävissä. Tutkimuksen tuloksia voidaan hyödyntää teoreettisesti ja käytännössä käännösyrityssimulaatioiden pedagogiikassa.